2012
DOI: 10.1093/icesjms/fss123
|View full text |Cite
|
Sign up to set email alerts
|

Size-related variation in fecundity of European eel (Anguilla anguilla)

Abstract: MacNamara, R., and McCarthy, T. K. 2012. Size-related variation in fecundity of European eel (Anguilla anguilla). – ICES Journal of Marine Science, 69: . Declining European eel (Anguilla anguilla) recruitment has focused attention on conservation of potential spawners leaving continental waters. Fecundity of wild, seaward-migrating silver-phase eels was shown to be size-related and higher than previously reported from artificial maturation experiments. Reliable information on fecundity is essential for stock m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 21 publications
2
35
1
Order By: Relevance
“…Some A. anguilla fecundity estimates have been obtained from hormone treated eels (e.g. Amin, 1998, see also Table 2 in MacNamara & McCarthy, 2012), but estimates from wild silver eels are limited to north-west Europe (from Ireland, Northern Ireland and England) and this study from the eastern Mediterranean (Greece). Fecundity estimates of 400 g silver eels from north-west Europe ranged between ca.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some A. anguilla fecundity estimates have been obtained from hormone treated eels (e.g. Amin, 1998, see also Table 2 in MacNamara & McCarthy, 2012), but estimates from wild silver eels are limited to north-west Europe (from Ireland, Northern Ireland and England) and this study from the eastern Mediterranean (Greece). Fecundity estimates of 400 g silver eels from north-west Europe ranged between ca.…”
Section: Discussionmentioning
confidence: 99%
“…MacNamara & McCarthy, 2012), only eels with an eye index >6.5 (Pankhurst, 1982) and GSI >1.2% (Durif et al, 2005) were considered for fecundity analysis.…”
Section: [ { ( Right Horizontal Eye Diameter + Right Vertical Eye Diamentioning
confidence: 99%
See 2 more Smart Citations
“…It is often found that F2 hybrids show reduced fitness because of disruption of sets of co-adapted genes by recombination that occurs in the second or later generations when assortment of alleles at different loci takes place (Gharrett and Smoker, 1991;Johnson et al, 2010). Eels are highly fecund, with an estimated mean fecundity of 3.6 million of eggs per female (MacNamara and McCarthy, 2012); therefore, even though the expected proportion of heterozygous loci in first-generation backcrosses is 50%, there will be variance around this number. In a large number of offspring from a single cross, there would consequently be some individuals that show high heterozygosity for diagnostic alleles at loci that presumably are under selection.…”
Section: Patterns Of Hybridizationmentioning
confidence: 99%